A new species of Marasmius from northern Argentina - Lechner, Bernardo Ernesto (2012)
Marasmius tyrius is proposed as a new species. It is characterized by collariate lamellae, insititious stipe, violet pileus, pileipellis with Siccus-type broom cells, and clavate to fusoid spores. Detailed description and illustrations of macro- and microscopic characters are provided.